Carbon sequestration and utilization in cement-based materials and potential impacts on durability of structural concrete - Meng, Dan (2023)
This paper reviews recent research development on carbon sequestration in cement-based materials, including accelerated carbonation technologies involving Portland cement (PC)-based materials, industrial wastes, and microbial approaches with carbonic anhydrase-producing bacteria and photosynthetic microbes. Different carbonation technologies are presented, including pre-carbonation during concrete mixing, and accelerated carbonation during concrete curing. The influence of these approaches in refining the microstructure and improving the mechanical properties, water resistance and crack healing potential of concrete materials is highlighted. In addition, a quantitative analysis was performed on the carbon sequestration capacity of PC-based materials and industrial wastes. The average CO2 uptake capacities ​​of PC-based materials and industrial wastes reported in previous studies are relatively low (14.4% and 10.6%, respectively), suggesting that there is still room for optimizing the carbonation process to further improve the reaction efficiency. Finally, the role of large-scale curing facilities utilizing industrial exhaust gas, such as autoclave systems or flow-through CO2 curing systems, in enabling the widespread implementation of CO2 sequestration in concrete products is discussed. Overall, this review aims to provide a roadmap for the academia and industry on how to improve the current carbonation technologies, their efficiency and the performance of concrete materials.